Rare association of epidermoid cyst of ovary with mucinous cystadenoma- A Case Report - Qayoom, Zunaira; Yaqoob, Nausheen (Journal of the Pakistan Medical Association, 2023)
Epidermoid cyst is a rare benign neoplasm of the ovary, lined by stratified squamous epithelium, lacking skin, adnexal structures, and other teratomatous elements. On the other hand, mucinous cystadenoma is one of the most common benign ovarian neoplasm that microscopically shows cystic areas lined by tall columnar mucinous epithelium. Although its coexistence with other tumours, such as mature cystic teratoma, squamous cell carcinoma, clear cell adenocarcinoma, Brenner’s tumour, serous cystadenoma, etc., have been reported, a combination of benign epidermoid cyst and mucinous cystadenoma has rarely been documented in literature. We report a case of coexistence of epidermoid cyst and mucinous cystadenoma in an ovarian cyst. Key Words: Epidermoid cyst, Mucinous cystadenoma.